2013
DOI: 10.1038/hdy.2013.102
|View full text |Cite
|
Sign up to set email alerts
|

Home-loving boreal hare mitochondria survived several invasions in Iberia: the relative roles of recurrent hybridisation and allele surfing

Abstract: Genetic introgression from a resident species into an invading close relative can result from repeated hybridisation along the invasion front and/or allele surfing on the expansion wave. Cases where the phenomenon is massive and systematic, such as for hares (genus Lepus) in Iberia, would be best explained by recurrent hybridisation but this is difficult to prove because the donor populations are generally extinct. In the Pyrenean foothills, Lepus europaeus presumably replaced Lepus granatensis recently and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…This question can be addressed in different ways, depending on priors about species history and ecology and the function of the genes studied. Here we had a strong hypothesis of a south-north range expansion that could account for the geographically restricted and massive mitochondrial DNA introgression3151619. The signal of range expansion is clear in the Northern part where introgression is present, and weak considering only the South of the Peninsula, at the origin of range expansion and where mitochondrial introgression is absent (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This question can be addressed in different ways, depending on priors about species history and ecology and the function of the genes studied. Here we had a strong hypothesis of a south-north range expansion that could account for the geographically restricted and massive mitochondrial DNA introgression3151619. The signal of range expansion is clear in the Northern part where introgression is present, and weak considering only the South of the Peninsula, at the origin of range expansion and where mitochondrial introgression is absent (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…1; Supplementary Table S5). It follows the direction expected to have created a South-North gradient of increasing introgression, due to allele surfing and potentially repeated introgression along the invasion and hybridization front8, as evidenced in L. europaeus , in its Iberian range16. However, the sample of loci we used to infer range expansion is relatively small29 and should be treated as preliminary.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Ancient hybridization in areas in which L. timidus is currently locally extinct, such as in the Iberian Peninsula, left genetic traces in the native species, which is particularly visible in their mtDNA (Melo‐Ferreira et al ., ; Alves et al ., ). A recent genetic study has suggested that the current geographical distribution of mtDNA of L. timidus origin in the hare species from the Iberian Peninsula could be a testament to L. timidus distribution in the region during the LGM (Melo‐Ferreira et al ., ). The results reported here confirm this hypothesis from a macroecological perspective.…”
Section: Discussionmentioning
confidence: 97%
“…Considering this model of northward range replacement with hybridization of the resident L. timidus by an invading L. granatensis , two phenomena may have contributed to this structured pattern of introgression: (1) the fixation of different introgressed alleles by drift in the invasion front and amplification of these variants in the wave of colonization; and/or (2) recurrent hybridization with a structured L. timidus population along the invasion front. A recent molecular study suggested that recurrent hybridization was probably involved, and that the areas in which the introgressed haplotypes are currently found might thus represent the ancestral distribution of L. timidus in Iberia during the LGM (Melo‐Ferreira et al ., ). The results presented here agree with this hypothesis, by showing that the climatic favourability for the presence of L. timidus in northern Iberia during the LGM is correlated with the frequency of introgression (Fig.…”
Section: Discussionmentioning
confidence: 97%